Animal Models of Acute Exacerbations COPD: Mechanistic Insights and Translational Challenges - Dewi, Rika Sari; Wuyung, Puspita Eka; Louisa, Melva; Sandhiutami, Ni Made Dwi; Pratomo, Irandi Putra (Sciences of Pharmacy, 2026)
Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) represent critical events in disease progression, yet their complex pathophysiology remains incompletely understood. Understanding the mechanisms underlying these exacerbations is essential for developing effective therapeutic strategies and improving patient outcomes. This literature review aims to synthesize current knowledge on the cellular and molecular mechanisms driving acute exacerbations of COPD, highlighting the importance of utilizing appropriate animal models for future research. This review identified rodent models, particularly mice (C57BL/6 strain) and rats (Sprague-Dawley) are predominantly employed due to their genetic tractability and physiological relevance, with occasional use of guinea pigs for airway hyperresponsiveness studies. Combined approaches using cigarette smoke exposure followed by inflammatory triggers (LPS, viral infections) showed the highest translational relevance. Key pathophysiological mechanisms studied include neutrophilic inflammation, oxidative stress, airway remodelling, and mucus hypersecretion. Current animal models provide valuable insight into AECOPD pathophysiology but face limitations in fully recapitulating human disease complexity. Future directions should focus on incorporating comorbidities, aging, and standardized outcome measures.